Mobile application system using augment reality for supporting higher educational students - Hafsa, Sayera; Tawafak, Ragad M.; Mazlina, Abdul Majid; Alfarsi, G. (AIP Publishing, 2023)
Access to the Internet and the use of new systems or programs provide an excellent opportunity for the public to open and continuous education. Although study or learning by the Internet or new networks have become more practical and helpful for students, a practitioner and educator’s attention as a channel to deliver their instruction and stimulate researchers in educational institutes, human organizations and companies is needed. All are working to develop programs and systems that could be useful for educators. On the other hand, the design and development of programs and systems need functional and straightforward students’ techniques. Many developers and designers try to create and make new versions of these programs and systems. Now a days, while making a relationship between the designing, they are designing expert research to keep pace with development. This research implements a scholarship student’s system that will include most of the services required by students to make scholarship laws easy to understand. As per the behind values of the survey examination, it is clear from understudies’ answers that they thought to have an application to help them take care of issues and need their organization slightly and quickly. Thus, the aim was reached and the system was established in Oman.